PENGARUH PROSES FERMENTASI TERHADAP SIFAT ANTINUTRISI BIJI SAGA (ADENANTHERA PAVONINA LINN) - Lenny Sutedja (Jurnal Kimia Terapan Indonesia, 1991)
Research has been conducted to know whether the steps in the fermentation of saga bean (ADENANTHERA PAVONINA LINN) could decrease or eliminate the antinutraive property of saga bean. The saga bean was fermented with Rhizopus oligosporus L36 and Aspergillus oryzae M8 respectively, and the fermentation steps included cooking, soaking, dehulllng, steaming, inoculation and incubation for 24 until 72 hours at 30°C. Antinutritive assay using protozoa Tetrahymena pyriformis GL showed that cooking followed by soaking had decreased the antinutritive property of saga bean. Then the steaming process had increased the antinutritive property of saga bean. Sinaila, gJ'owth inhibition of protozoa was observed in medium containing steamed saga bean compared to that in medium containing fresh saga bean. Tempe saga, either fermented with R.oligosporus or A.oryzae, showed about 30-100% growth inhibition ofT.pyriformisGL, at a concentration of 103-104 ppm.